PENGARUH PUPUK KANDANG TERHADAP PERTUMBUHAN BEBERAPA VARIETAS BIBIT TANAMAN TEBU (Saccharum officinarum L.) DI POLYBAG - Amir, Nurbaiti; Hawalid, Heniyati; Nurhuda, Ismail Arifal (Universitas Muhammadiyah Palembang, 2017)
Manure on the Growth Effect of several varieties of seeds of sugarcane (Saccharum officinarum L.) in polybag. This research aims to study the Influence Manure on Growth of some varieties of seed sugarcane (Saccharum officinarum L.) in Polybag. This research has been conducted in the field experiment station C campus of University of Muhammadiyah Palembang, Hamlet 1,Semambu Island Village , North Indralaya districts Ogan Ilir regency, South Sumatra from April 2016 to July , 2016. This study uses a randomized block design (RAK) Factorial with 9 combination treatment and repeated 3 to 4 plants sample replicates . The treatment factors are as follows : (1) Manure (K) are: K1 Manure Chicken Manure , K2 Manure goat manure , K3 Manure Cow Manure, and (2) Varieties Sugarcane (V) ,namely : V1 Varieties Kidang chariot (KK),V2 Varieties PS 881 K2 , V3 PCSO 902 Varieties. The parameters observed in this study is Time bud (HST) , plant height cm , Number of tillers, Leaf Number (Overlay), Long Roots cm, Total Root. Based on the results of analysis of variance showed that the treatment of manure Cow Manure 20 tons / ha significantly affect the number of leaves and no real effect on all the observed variables. Treatment of PCSO 902 varieties manifest until very real effect on plant height, number of leaves, number of tillers and root length, but the effect was not significant to time out shoots and roots number.